PENGEMBANGAN SPEAKING SKILL MELALUI KEGIATAN VISITING FOREIGNERS - Astuti, Dwi Setyo; Setyowati, Eka Viola; Fadil, Zahratul; Adani, Fildzah Tita; Wijiastuti, Ayu (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The ability to speak English or speaking skills is one aspect of learning a language. There are various things that can be done to develop students' speaking skills, one of which is visiting foreigners conducted by SMK N 1 Banyudono in the English Conversation Club extracurricular activities. This is done so that students get a provision for communication in English so that when students graduate from school as graduates of vocational school students have provision of communication skills both in the native language and English as a foreign language. After this activity is carried out, a follow-up activity will be held, where students make reports and presentations about the conversations they have had so that students can evaluate the activities that have been carried out. Furthermore, this activity is considered quite important and must be continued in addition to developing speaking skills, this activity can also develop students' confidence.